Clinical study of chemotherapy induced febrile neutropenia: talcott’s versus multinational association for supportive care in cancer risk assessment scoring systems - Gaur, Rachana; Bhardwaj, Rahul; Sharma, Sandeep; Rathnam, Krishna Kumar (International Journal of Research in Medical Sciences, 2020)
Background: Cancer is a leading cause of death worldwide, accounting for 8.2 million deaths in 2012. Febrile neutropenia (FN) is fever associated with abnormally low neutrophil count signifying an immunocompromised state secondary to malignancy or its treatment. The aim of this study was to evaluate clinical outcome of chemotherapy induced febrile neutropenia. Methods: This was a hospital based prospective, descriptive observational study. Patients of either sex, age (18-90 years), with cancer on chemotherapy, single oral temperature ≥101°Fahrenheit (38.3°C) or a temperature ≥100.4° Fahrenheit (38.0° C) for ≥ one hour with absolute neutrophil counts <500 cells/mm3 or <1000 cells/mm3 with a predicted decrease to less than 500 cells/mm3 in the next 24 hours, only with first febrile episode occurring during study period and prior or concurrent radiation therapy were included in this study. Results: Among 87 patients, 70 (80.5%) were less than 60 years and 17 (19.5%) were ≥60 years. The mean age of study patients was 44.46±15 years, (range 18 to 77 years), 31(35.6%) were male and 56 (64.4%) were female. Talcott’s and MASCC risk predicting tool versus outcome, p values for Talcott’s and MASCC were significant (<0.05). Conclusions: Neutropenic fever is a potentially life-threatening complication of cancer chemotherapy. MASCC and Talcott’s model can be used to identify low and high risk patients. MASCC risk index may have a better performance than the Talcott’s model in risk classification.